2008
DOI: 10.1194/jlr.m700275-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

The trans-10, cis-12 isomer of conjugated linoleic acid decreases adiponectin assembly by PPARγ-dependent and PPARγ-independent mechanisms

Abstract: The adipocyte-derived secretory protein adiponectin functions as an insulin-sensitizing agent. In plasma, adiponectin exists as low, medium, and high molecular weight oligomers. Treatment with trans -10, cis -12 conjugated linoleic acid (t-10, c-12 CLA) reduces levels of adiponectin as well as triglyceride (TG) in mice and adipocyte cell culture models. The aim of this study was to determine whether the effects of t -10, c -12 CLA on adiponectin and TG are mediated through modulation of the transcription facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 56 publications
2
36
0
4
Order By: Relevance
“…Activation of PPARγ by TZD induces adiponectin gene expression in 3T3-L1 adipocytes [22], while PPARγ activation has an inverse correlation with leptin gene expression, as reported in previous studies [30][31][32][33]. GW9662 is known as a potent and selective PPARγ antagonist and has been used to specifically block PPARγ activation in many studies [34][35][36]. Although it has also been reported that GW9662 might act through other PPARγ-independent pathways, selectively antagonizing PPARγ activity is the primary action of GW9662 [37].…”
Section: Discussionmentioning
confidence: 79%
“…Activation of PPARγ by TZD induces adiponectin gene expression in 3T3-L1 adipocytes [22], while PPARγ activation has an inverse correlation with leptin gene expression, as reported in previous studies [30][31][32][33]. GW9662 is known as a potent and selective PPARγ antagonist and has been used to specifically block PPARγ activation in many studies [34][35][36]. Although it has also been reported that GW9662 might act through other PPARγ-independent pathways, selectively antagonizing PPARγ activity is the primary action of GW9662 [37].…”
Section: Discussionmentioning
confidence: 79%
“…Conjugated linoleic acid (CLA) and Arginine (Arg) are two typical agents of this kind commonly used in the livestock industry. Previous studies have reported CLA can decrease the body fat mass (West et al, 1998; Sisk et al 2001; Meadus et al, 2002) and increase the lean body mass (House et al, 2005; Gaullier et al, 2007) through suppressing the expression of PPARγ (Kang et al, 2003), inhibiting the convertion of preadipocyte into adipocyte (Miller et al, 2008). Arg has also been reported to have the capacity to decrease the body fat accretion and enhance the muscle gain (He et al, 2009; Tan et al, 2009), which involves multiple NO-dependent pathways (Jobgen et al, 2006), and also correlated to the functions of PPARγ (Vasilijevic et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…CLA inhibits adipogenesis -the conversion of preadipocytes into adipocytes involves the activation of key transcription factors such as peroxisome proliferator-activated receptor γ (PPARγ) and CAAT/enhancer binding protein (C/EBP). There is evidence that CLA suppresses preadipocyte differentiation in animals (Di Giancamillo et al 2007;Miller et al 2008) and humans (Brown et al 2004) preadipocytes. CLA increases inflammation -although the primary function of white adipose tissue is energy storage, it also has the ability to produce a number of proinflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%